THE EFFECT OF TUI NA MASSAGE ON IMPROVING APPETITE AMONG CHILDREN AGED 2–4 YEARS - Dyah Ayu Wulansari; Rani Safitri; Anik Sri Purwanti (Poltekkes Kemenkes Pontianak, 2026)
Background: Many toddlers often have difficulty eating, and this is a common problem. One of the most common is decreased appetite. The impact of this is very dangerous, it can cause malnutrition, growth and developmental disorders, and the risk of stunting. If not addressed immediately, this problem can continue until preschool age. Purpose: This study aims to analyze the effect of Tui Na massage on increasing the appetite of toddlers aged 2-4 years at KB Putra Harapan and KB Baytul Makmur, Bululawang District, Malang Regency. Methods: This study employs a pre-experimental design using a one-group pretest-posttest approach. Results: The results are expected to provide scientific evidence on the effectiveness of Tui Na massage as a non-pharmacological intervention to overcome the problem of poor appetite in toddlers. The study showed that Tui Na massage significantly increased the appetite of toddlers aged 2-4 years in KB Putra Harapan and KB Baytul Makmur, Bululawang District, Malang Regency. Most of the toddlers who were respondents experienced an increase in appetite after receiving this intervention. Conclusion This shows that Tui Na massage can be an effective and safe non-pharmacological alternative to overcome toddler appetite problems. This method can be recommended as a promotive and preventive effort to support optimal child growth and development, and can be applied by health workers and parents in early childhood education environments